Figure of community support in achieving Muhammadiyah school autonomy progress - Mohamad Joko Susilo; Badrun Kartowagiran; Dwi Sulisworo (Institute of Advanced Engineering and Science, 2019)
School autonomy can not be separated from support factor. This study aimed to determine source and form of community support and contribution in realizing autonomous in Muhammadiyah schools. This research development is part of dissertation conducted with five stages: define, design, model development, model validation, and model use. The study was conducted at SMP Muhammadiyah, Sleman Regency, with 280 respondents; consist of principals, teachers, staff, students, and ministerial assemblies of Dikdasmen. Data collection technique used: interviews, questionnaires, and documentation. Data analysis techniques use quantitative inferential analysis, EFA and CFA techniques. The results showed that form and source of support for Muhammadiyah schools is internal as well as external. School support also comes from internal and external support, such as: committee, parents, stakeholders, foundation, education official, collages, and related institutions. Directly and indirectly effect, contribution of school supporting component (Bac) to be school autonomous (Kms) up to 0.30.